Successful correction of the transverse vaginal septum with a pinhole vaginal foramen using YV plasty: A case report - Misako Yamamoto; Shunsuke Kawahara; Ryusuke Murakami; Ayano Honda; Itaru Tsuge; Mana Taki; Koji Yamanoi; Ken Yamaguchi; Junzo Hamanishi; Masaki Mandai (Case Reports in Women's Health, 2024)
The transverse vaginal septum, a rare Müllerian duct anomaly, presents diagnostic and therapeutic challenges owing to its variable location, thickness, and potential association with uterine malformations. Therefore, an accurate diagnosis and selection of an appropriate treatment are important. Herein, the case of a 28-year-old nonpregnant woman with sexual dysfunction attributable to a transverse vaginal septum is presented. The septum, approximately 5 mm thick, was situated low on the vaginal wall near the urethral opening, with a small central aperture. Employing YV plasty, full extension of the posterior and lateral vaginal walls was achieved while minimizing the manipulation of the anterior wall to avoid urethral injury. Postoperatively, the patient achieved sexual function without vaginal stenosis. YV plasty is a minimally invasive and effective approach for preventing postoperative stenosis in the treatment of a thin transverse vaginal septum located low on the vaginal wall.